MCSA/MCSE Self-Paced Training Kit (Exam 70-200): Managing and Maintaining a Microsoft Windows server 2003 environment - Holme Dan (Microsoft Press, 2003)
Ace your exam preparation and ramp up quickly on Windows Server 2003 by working at your own pace through the lessons, hands-on exercises, and practice tests. The Readiness Review Suite on CD, featuring advanced technology from MeasureUp, provides 425 challenging questions for in-depth self-assessment and practice. Choose timed or untimed testing mode, generate random tests, or focus on discrete objectives or chapters, and get detailed explanations for right and wrong answers—including pointers to other sources for further study. You also get a 180-day evaluation version of Windows Server 2003 software and a 15 percent exam discount voucher—making this kit an exceptional value and a great career investment.